Contactless cards: How technology works and how to protect unauthorized transactions using a ‘armored’ card holder - Mororó, Alisson Emanuel Silva; Silva , Jainara de Jesus; Oliveira, Danielle Aparecida da Silva (Seven Editora, 2023)
Contactless technology was implemented in magnetic cards to facilitate financial transactions between customers and merchants. One of the problems is that: because it is a technology capable of making payments without the need for a password, many people end up choosing not to use such technology for fear of carrying out transactions without consent. Therefore, this work aims to disseminate the operation of NFC applied to magnetic cards and a tutorial on how to produce a low-cost “armored” card holder. Therefore, it is important that people are informed about the technology so that they can protect themselves and do not stop using it, facilitating and speeding up their financial transitions and that they do not need to contact the terminal, preventing the proliferation of viruses and bacteria. Digital materials were produced for digital platforms using two animation software addressing the explanation and operation of the technology. An armored card holder was also produced, creating an assembly tutorial, using cardboard, cardboard, aluminum foil and tools such as scissors, ruler, etc. As a result, 03 shared publications were obtained, these publications took the information to some people who were afraid to use the resource. Therefore, with this work it was noticed that people need to be well informed about new technologies, especially those that facilitate their daily lives. In addition, it is important that science has a language that is more accessible to the lay public, so that it does not fall into superficial, even false, information and end up being held hostage by outdated procedures.DOI:https://doi.org/10.56238/alookdevelopv1-184